2013
DOI: 10.1016/j.joca.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The association between hip bone marrow lesions and bone mineral density: a cross-sectional and longitudinal population-based study

Abstract: Hip BMLs were associated with local BMD (hip and femoral neck) but not with spine BMD and these associations vary according to site. BML prevalence and change was low in this study, hence these findings need confirmation. However, we hypothesize that these associations represent a combination of changes related directly to the BML pathology or changes adjacent to the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
(28 reference statements)
0
12
1
Order By: Relevance
“…reported that transient bone marrow edema (TBME) in the foot and ankle was strongly associated with low systemic BMD; however, the sample size in this study was small ( n = 10). Ahedi et al . found that hip BMLs were associated with local BMD (hip and femoral neck) but not with distant spine BMD; however, the prevalence of hip BMLs was low in this study.…”
Section: Discussioncontrasting
confidence: 88%
“…reported that transient bone marrow edema (TBME) in the foot and ankle was strongly associated with low systemic BMD; however, the sample size in this study was small ( n = 10). Ahedi et al . found that hip BMLs were associated with local BMD (hip and femoral neck) but not with distant spine BMD; however, the prevalence of hip BMLs was low in this study.…”
Section: Discussioncontrasting
confidence: 88%
“…Modes 2 and 4 appear to be strongly associated with structural changes in the subchondral bone of the hip, which are risk factors for the progression of OA . For instance, at baseline, lower scores of these modes were associated with greater JSN and prevalence of osteophytes, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Quantitative assessment of subchondral hip BMLs in STIR MRI images was done using OsiriX software (Mac version, University of Geneva). BMLs were identified as areas of increased signal intensity adjacent to the subchondral bone on the femoral head and/or the acetabulum .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations